Dissecting the Local Environment of FRB 190608 in the Spiral Arm of its Host Galaxy - Chittidi, Jay S; Simha, Sunil; Mannings, Alexandra; Prochaska, J Xavier; Ryder, Stuart D; Rafelski, Marc; Neeleman, Marcel; Macquart, Jean-Pierre; Tejos, Nicolas; Jorgenson, Regina A; Day, Cherie K; Marnoch, Lachlan; et al. (arXiv.org, 2021)
We present a high-resolution analysis of the host galaxy of fast radio burst (FRB)~190608, an SB(r)c galaxy at \(z=0.11778\) (hereafter HG 190608), to dissect its local environment and its contributions to the FRB properties. Our Hubble Space Telescope Wide Field Camera 3 ultraviolet and visible light image reveals that the subarcsecond localization of FRB~190608 is coincident with a knot of star-formation (\(Σ_{\rm SFR} = 1.5 × 10^{-2}~ M_{\odot} \, \rm \, yr^{-1} \, kpc^{-2}\)) in the northwest spiral arm of HG~190608. Using H\(β\) emission present in our Keck Cosmic Web Imager integral field spectrum of the galaxy with a surface brightness of \(μ_{\rm Hβ}= \mathrm{(3.36±0.21)×10^{-17}\;erg\;s^{-1}\;cm^{-2}\;arcsec^{-2}}\), we infer an extinction-corrected H\(α\) surface brightness and compute a dispersion measure (DM) from the interstellar medium of HG 190608 of \(\rm DM_{\rm Host,ISM} = 94 ± 38~ \;pc\;cm^{-3}\). The galaxy rotates with a circular velocity \(v_{\rm circ} = \rm 141 ± 8~ km\;s^{-1}\) at an inclination \(i_{gas} = 37 ± 3^°\), giving a dynamical mass \(M_{\rm halo}^{\rm dyn} ≈ 10^{11.96 ± 0.08}~M_{\odot}\). This implies a halo contribution to the DM of \(\rm DM_{\rm Host,Halo}= \rm 55±25 \;pc\;cm^{-3}\) subject to assumptions on the density profile and fraction of baryons retained. From the galaxy rotation curve, we infer a bar-induced pattern speed of \(Ω_p=34± 6\;\mathrm{km\;s^{-1}\;kpc^{-1}}\) using linear resonance theory. We then calculate the maximum time since star-formation for a progenitor using the furthest distance to the arm's leading edge within the localization, and find \(t_{enc} = 21_{-6}^{+25}\) Myr. Unlike previous high-resolution studies of FRB environments, we find no evidence of disturbed morphology, emission, or kinematics for FRB 190608.